Analysis and proposals for optimization of transfer pricing illustrated on a specific business organisation - Hoferek, Filip (2021)
This thesis concentrates on analysis and proposals for optimization of transfer pricing inside the specific corporate. The study consists of three sections. In the first one, basic introduction of the company is given, whereas the second part offers basic terms and approaches to the specific topic. The last section describes the current transfer pricing policies inside the company and, if needed, suggests alternative attitudes of how to approach the optimization in accordance with the theoretical approaches in the specific situation faced by the business.